Atg2: A novel phospholipid transfer protein that mediates de novo autophagosome biogenesis. (29th April 2019) - Osawa, Takuo; Noda, Nobuo N.
Abstract: The degradation of cytoplasmic components via autophagy is crucial for intracellular homeostasis. In the process of autophagy, a newly synthesized isolation membrane (IM) is developed to sequester degradation targets and eventually the IM seals, forming an autophagosome. One of the most poorly understood autophagy‐related proteins is Atg2, which is known to localize to a contact site between the edge of the expanding IM and the exit site of the endoplasmic reticulum (ERES). Recent advances in structural and biochemical analyses have been applied to Atg2 and have revealed it to be a novel multifunctional protein that tethers membranes and transfers phospholipids between them. Considering that Atg2 is essential for the expansion of the IM that requires phospholipids as building blocks, it is suggested that Atg2 transfers phospholipids from the ERES to the IM during the process of autophagosome formation, suggesting that lipid transfer proteins can mediate de novo organelle biogenesis.